2020
DOI: 10.4038/jula.v23i2.8007
|View full text |Cite
|
Sign up to set email alerts
|

User Satisfaction on library resources and services: survey conducted in main library of the Open University of Sri Lanka

Abstract: One of the most important measures used for evaluating the service quality of a library is a user satisfaction survey. The objectives of the study were to find out the purposes of using a library and to evaluate user satisfaction towards the library facilities, library staff, library services, library resources and library website of the Open University of Sri Lanka. The population of the study was the university staff and the students who registered in the library of the Colombo regional centre of the Open Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 4 publications
1
2
1
Order By: Relevance
“…In relation to employee affection (H4), the results of this research indicated that it does not have a significant influence on user satisfaction, which is different from previous studies [4], [42], [43], [44], [45]. These findings could be due to the fact that, while friendly and empathetic treatment by staff is important [46], it is not a major factor in determining users' satisfaction with the virtual library service.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In relation to employee affection (H4), the results of this research indicated that it does not have a significant influence on user satisfaction, which is different from previous studies [4], [42], [43], [44], [45]. These findings could be due to the fact that, while friendly and empathetic treatment by staff is important [46], it is not a major factor in determining users' satisfaction with the virtual library service.…”
Section: Discussioncontrasting
confidence: 89%
“…• H1: The quality of the system influences satisfaction • H2: The quality of information influences satisfaction • H3: The quality of services influences satisfaction The ability and responsiveness of an employee has an impact on user satisfaction [42]. Therefore, the competencies and behaviour of library staff are relevant to user satisfaction [42], [43], so when employees show appreciation, care and kindness towards users, it can improve the service experience and increase user satisfaction [4], [44]. The work environment, including factors such as situational leadership and motivation, can also influence employee job satisfaction, which in turn affects library user satisfaction, because if employees are happy in their work environment, they are more likely to be committed and motivated in their roles, offering better customer service and a more positive interaction with library users [44].…”
Section: Satisfaction and Loyalty In Librariesmentioning
confidence: 99%
“…Respondents strongly agreed or agreed that library staff was friendly and helpful 91% (336), experienced and well trained 85% (315) and responds effectively and efficiently to users' requirements 80% (300). These findings were in par with results of the studies conducted by Gunasekara (2010), Sivathaasan (2013), Vijeyalaxmy (2015 and Amarasekara and Marasinghe (2020).…”
Section: Undergraduates Perceptions On Library Staffsupporting
confidence: 85%
“…University libraries play a major role in providing information resources required for teaching, learning and research purposes of their community (Amarasekara & Marasinghe, 2020). Currently, academic libraries are facing great challenges due to the global digital revolution.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, structure and style of library websites more or less continue to stay as they were during the periods what people called 'normal days.' In a recent survey, it was found that users are highly satisfied only with library catalogue, past examination papers and electronic databases accessed through the websites (Amarasekera & Marasinghe, 2020). In an ever-changing digital world library users may expect even more dynamic web interfaces to exploit information although they are satisfied with existing web-based resources and services.…”
Section: Background Of the Studymentioning
confidence: 99%